Sexually acquired hepatitis C virus infection: a review. (August 2016) - Chan, Denise P.C.; Sun, Hsin-Yun; Wong, Horas T.H.; Lee, Shui-Shan; Hung, Chien-Ching
Highlights: The transmission of hepatitis C virus (HCV) is increasing within the specific core group of men who have sex with men (MSM) because of increased sexual risk behaviours, including serosorting on the basis of HIV-positive status, chemsex, and intense mucosally traumatic sexual practices. The advent of direct-acting antivirals has improved treatment responses of HCV infection significantly; however, sexually transmitted HCV reinfections occur in a substantial proportion of HIV-positive MSM following clearance of a primary infection. Effective screening and preventive strategies tailored to the MSM communities are needed to facilitate the control of sexually acquired HCV infection. Summary: Sexually acquired hepatitis C virus (HCV) infection remains a public health problem, with significant disease burden primarily in HIV-positive men who have sex with men (MSM). Over the past decades, the epidemic of sexually transmitted HCV infection has continued to expand and the epidemiology of HCV in HIV has changed significantly. In the post-combination antiretroviral therapy era, sexual network characteristics within the specific core group of MSM with increased sexual risk behaviours, including serosorting on the basis of HIV-positive status and intense mucosally traumatic sexual practices, confer increased HCV acquisition and transmission. This review summarizes the current epidemiology of sexually acquired HCV infection and the clinical and immunological contexts of acute HCV infection, and describes the biological, social, and behavioural factors that have facilitated permucosal transmission of HCV in MSM. While the advent of direct-acting antivirals has improved treatment responses significantly, sexually transmitted HCV reinfections occur in a substantial proportion of HIV-positive MSM following clearance of a primary infection. Effective strategies and preventive interventions that are tailored to the MSM communities to facilitate the control of sexually acquired HCV infection cannot be overemphasized.